Dialysis for acute kidney injury associated with influenza a (H1N1) infection - Augusto Vallejos; Marcelo Arias; Ana Cusumano; Eduardo Coste; Miguel Simon; Ricardo Martinez; Sandra Mendez; Miguel Raño; Luis Sintado; Bruno Lococo; Carlos Blanco; Jorge Cestari (Saudi Journal of Kidney Diseases and Transplantation, 2013)
In June 2009, the World Health Organization declared a novel influenza A, S-OIV (H1N1), pandemic. We observed 44 consecutive patients during the "first wave" of the pandemic. 70.5% of them showed co-morbidities (hypertension, obesity, chronic respiratory diseases, chronic renal disease, diabetes, pregnancy). Serious cases were admitted to the intensive care unit (ICU), particularly those with severe acute respiratory failure. Some of them developed acute kidney injury (AKI) and required renal replacement therapy (RRT). The average time between admission to the ICU and initiation of RRT was 3.16 ± 2.6 days. At initiation of RRT, most patients required mechanical ventilation. No relationship was found with creatinine-kinase levels. Seventy-five percent of the cases were observed during a 3-week period and mortality, related to respiratory failure, doubling of alanine amino transferase and use of inotropics was 81.8%. In conclusion, the H1N1-infected patients who developed RRT-requiring AKI, in the context of multi-organ failure, showed a high mortality rate. Thus, it is mandatory that elaborate strategies aimed at anticipating potential renal complications associated to future pandemics are implemented.